Exploring multiple mechanisms of Qingjie Fanggan prescription for prevention and treatment of influenza based on systems pharmacology. (October 2020) - Gao, Kai; Song, Yan-Ping; Du, Xia; Chen, Hao; Zhao, Lin-Tao
Graphical abstract: Highlights: Systems pharmacology could solve complex pharmacological problems. Qingjie Fanggan prescription fight influenza by multi-component-target-pathway mode. The components of Qingjie Fanggan prescription have good docking activity with ERKs. Abstract: Influenza is a type of acute disease characterized by strong contagiousness and short incubation period, which have posed a large potential threat to public health. Traditional Chinese Medicine (TCM) advocates to the aim of combating complex diseases from a holistic view, which has shown effectiveness in anti-influenza. However, the mechanism of TCM prescription remains puzzling. Here, we applied a system pharmacology approach to reveal the underlying molecular mechanisms of Qingjie Fanggan prescription (QFP) in the prevention and treatment of influenza. In this study, we identified 228 potential active compounds by means of absorption, distribution, metabolism, and excretion (ADME) evaluation system and literature research. Then, the targets of the potential active compounds were predicted by using the WES (Weighted Ensemble Similarity) method, and the influenza-related targets were obtained according to some existing gene databases. Next, an herb-component-target network was constructed to further dissect the multi-directional therapeutic approach for QFP. Meanwhile, we also performed gene ontology (GO) enrichment analysis and Kyoto Encyclopedia of Genes and Genomes (KEGG) annotation analysis on 344 potential targets. Finally, a target-pathway network was constructed to further dissect the core pathways and targets in treatment of influenza for QFP. And the key components and targets were docked by AutoDock Vina to explore their binding mode. All of these demonstrated that QFP had multi-scale curative activity in regulating influenza-related biological processes, which facilitates the application of traditional medicine in modern medicine.